The Effect of Augmented Reality Use on Student Understanding in Teaching the Sense of Sight in Elementary School - Hardiansyah, Framz; Ramadana, Tria Novita; Rofiko, Sefti; Imaniyah, Dita; Rahman, Moh Ainur (Journal of Practice Learning and Educational Development, 2025)
This research aims to find out how the use of augmented reality learning media affects students' understanding of science subjects, namely the five senses of sight. This research used a pre-experimental quantitative approach with One Group Pretest Posttest Design. The subjects in the research were the class III homeroom teacher and 19 students at SDN Pangarangan III. Data collection carried out included interviews, media tests, pretests and posttests. This research activity was carried out in three meetings, namely in the first meeting there was an interview with the class 3A teacher to find out what problems existed in the class. Next is the second meeting, namely a discussion about the media that the author has created for the homeroom teacher. Followed by the third meeting, namely conducting a trial of augmented reality media and then carrying out pretest work and posting it online. The results of this research show that there is a positive influence on students' understanding of science material from the use of augmented reality learning media. It can be concluded that the use of this media can increase students' understanding of the subject matter because the N-Gain score test analysis produces an average score of 0.37 so it is included in the "medium" group.